2013
DOI: 10.1016/j.matlet.2013.06.031
|View full text |Cite
|
Sign up to set email alerts
|

One-pot green synthesis of Ag nanoparticles-decorated reduced graphene oxide for efficient nonenzymatic H2O2 biosensor

Abstract: (2013). One-pot green synthesis of Ag nanoparticles-decorated reduced graphene oxide for efficient nonenzymatic H2O2 biosensor. Materials Letters, 107 (15 September), 311-314.One-pot green synthesis of Ag nanoparticles-decorated reduced graphene oxide for efficient nonenzymatic H2O2 biosensor AbstractAg nanoparticles (AgNP) with an average size of 12 nm are successfully decorated on the reduced graphene oxide (rGO) sheets through a simple one-pot hydrothermal method using gallic acid as the reducing agent. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…This would decrease CAO with sp 3 -hybridized orbitals, thus the sp 2 /sp 3 ratio of carbon atoms increased in XPS profiles of C1s, which was consistent with the result in literature [34]. Moreover, the formation of Ag particles facilitated the transformation of carbon atoms from sp 3 -hybridized orbitals to sp 2 -hybridized orbitals, similar to reports in the literature [35].…”
Section: Surface Properties Of Different Ag-go Samplessupporting
confidence: 91%
See 1 more Smart Citation
“…This would decrease CAO with sp 3 -hybridized orbitals, thus the sp 2 /sp 3 ratio of carbon atoms increased in XPS profiles of C1s, which was consistent with the result in literature [34]. Moreover, the formation of Ag particles facilitated the transformation of carbon atoms from sp 3 -hybridized orbitals to sp 2 -hybridized orbitals, similar to reports in the literature [35].…”
Section: Surface Properties Of Different Ag-go Samplessupporting
confidence: 91%
“…S3. From this figure, the as-synthesized GO displayed a typical characteristic (0 0 2) peak at about 10.8° [34]. From XRD patterns of three Ag-GO samples, it could be found that the characteristic peak of Ag-GO samples showed obviously weaker than that of GO sample.…”
Section: Morphology Of Different Ag-go Samplesmentioning
confidence: 85%
“…However, it is a chemically inactive element, but it can be reacted with nitric acid or hot concentrated sulfuric acid, forming soluble silver salts. It also possesses an excellent conductivity of heat and electricity, yet its applications in electrical industry have greatly been limited due to its greater cost (Wang et al 2013). As for metallic silver form, it is insoluble in water, but its metallic salts such as silver nitrate, AgNO 3 , and silver chloride, AgCl, are water-soluble.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Non-enzyme electrochemical sensors have been fabricated which are based on composite graphene with metal nanoparticles such Au [20] and Ag [21]. Also Hybridization of the graphene and Fe in the form of Fe 2 O 3 or Fe 3 O 4 hasbeen extensively studied for various applications such as H 2 O 2 detection because of abundant, low cost, and nontoxic material.…”
mentioning
confidence: 99%